Temporal profile of HEV RNA concentration in blood and stool from patients with acute uncomplicated hepatitis E in a region with genotype 1 predominance. Issue 6 (12th February 2020) - Goel, Amit; V. Padmaprakash, Kodavoor; Benjamin, Mercilena; Katiyar, Harshita; Aggarwal, Rakesh
Abstract: Acute hepatitis E virus (HEV) is associated with viremia and faecal excretion of the virus. The information on duration and temporal pattern of viremia and faecal shedding in HEV infection is important, but is not available. Serial serum and stool specimens were collected from patients with acute hepatitis E (typical clinical picture, serum alanine aminotransferase levels > 5‐folds the upper limit of normal and presence of IgM anti‐HEV), beginning from within 7 days of the onset of symptoms. HEV RNA concentrations were measured in sera and 10% stool suspensions, using a real‐time Taqman‐based nucleic acid amplification assay. Seventeen patients (median age 25 [range 19‐61] years; all men) were enrolled within a median of 5 (range 3‐8) days of the onset of the first symptom and provided 113 serum specimens and 71 stool specimens. The median (range) highest levels of serum bilirubin, alanine aminotransferase and aspartate aminotransferase in the patients were 10.3 (5.9‐43.4) mg/dL, 1817 (442‐4642) IU/L and 1016 (88‐4561) IU/L, respectively. All the 17 patients had demonstrable viremia, and 12 of the 13 patients who were tested had faecal excretion at one or more time points. The HEV RNA titres were the highest in the early phase of disease and declined rapidly with time, becoming nondetectable in the serum by day 20 and in the stool by day 21. In most of the patients with acute uncomplicated acute hepatitis E, the degree of viremia and faecal shedding decline quickly after the onset of clinical illness and rapidly disappear in parallel with each other.